Polyphenols in the Fermentation Liquid of Dendrobium candidum Relieve Intestinal Inflammation in Zebrafish Through the Intestinal Microbiome-Mediated Immune Response - Gong, Xiaoyue; Jiang, Shuaiming; Tian, Haiyan; Xiang, Dong; Zhang, Jiachao (Frontiers in Immunology, 2020)
Previous studies of Dendrobium candidum (D. candidum), which is mainly distributed in tropical areas, have mainly focused on its functional polysaccharide; the effects of D. candidum polyphenols, the chemical composition of which may be improved by fermentation, have received limited attention, especially in in vivo models, which inevitably involve interactions with intestinal microorganisms. To address this challenge, metagenomic and metabolomic techniques, were applied, and immune factors and mucosal barrier-related proteins were determined to reveal the effects of fermented D. candidum polyphenols (FDC) on intestinal inflammation induced by oxazolone in zebrafish. The results showed that fermentation significantly changed the chemical composition of D. candidum and that FDC significantly improved the intestinal immune index. After the 21st day of FDC intervention, the abundance of Lactobacillus, Faecalibacterium and Rummeliibacillus increased, but the abundance of the genera Shewanella, Geodermatophilus, Peptostreptococcaceae and Mycobacterium decreased. At the same time, FDC significantly increased intestinal short-chain fatty acids (SCFAs). In addition, network analysis based on multi-omics indicated that FDC intake leads to changes in intestinal microbiota and intestinal metabolites, resulting in enhanced host immune function. These results indicate that FDC can improve intestinal health by regulating the intestinal microbiota and its metabolites to treat intestinal inflammation and regulate the host immune system. The present research improved our understanding of the utilization of D. candidum polyphenols and provided new evidence for the impacts of fermented D. candidum on host health.